Monitoring of Blood Pressure is not Enough to Avoid Neonatal Postoperative Encephalopathy - Lubián López, Simón Pedro; Zuazo Ojeda, Amaya; Jimenez Gómez, Gema; Benavente Fernández, Isabel (American Journal of Perinatology Reports, 2018)
Background Neonatal encephalopathy with seizures after general anesthesia not occurring in infants undergoing cardiac or major neurosurgery is very uncommon. An ischemic origin due to cerebral hypoperfusion from perioperative hypotension has been suggested, but there is a lack of a consensus definition for intraoperatory hypotension in neonates.Case Report We report the first case of neonatal encephalopathy with seizures in a neonate with anorectal malformation. He underwent a colostomy with caudal anesthesia combined with light general anesthesia. Intraoperative systolic blood pressure and mean blood pressure values were considered normal. Thirty-two hours after the intervention, the patient presented electroclinical seizures. Diffusion-weighted imaging showed bilateral involvement with reduced diffusivity in the watershed areas of the middle cerebral artery and posterior cerebral artery.Conclusion Perioperative monitoring of blood pressure is not enough in neonatal surgery. Cerebral magnetic resonance imaging should be considered in infants with noncardiac congenital anomalies after neonatal surgery and long-term follow-up is required.
Keywords: encephalopathy; postoperative; hypotension; caudal anesthesia; diffusion-weighted imaging; neonate